2011
DOI: 10.1007/s00360-011-0612-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in partial pressures of respiratory gases during submerged voluntary breath hold across odontocetes: is body mass important?

Abstract: Odontocetes have an exceptional range in body mass spanning 10(3) kg across species. Because, size influences oxygen utilization and carbon dioxide production rates in mammals, this lineage likely displays an extraordinary variation in oxygen store management compared to other marine mammal groups. To examine this, we measured changes in the partial pressures of respiratory gases ([Formula: see text], [Formula: see text]), pH, and lactate in the blood during voluntary, quiescent, submerged breath holds in Paci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…Across air-breathing, diving vertebrates, including three odontocetes, which included beluga (Noren et al, 2012), shallow diving emperor penguins (Aptenodytes forsteri; Ponganis et al, 2010) and freely diving Weddell seals (Leptonychotes weddelli; Castellini et al, 1992;Ponganis et al, 1993), a cADL that assumed an oxygen consumption rate of 2× Kleiber basal metabolic rate (BMR; Kleiber, 1975) best approximated experimentally determined ADLs. Thus, we assumed a diving metabolism of 2×BMR, as used for other cetaceans (Noren et al, 2002(Noren et al, , 2014, to estimate age-specific maximum breath-hold limits and bottom times at various dive depths, where BMR (l O 2 min −1 ) is 0.0101×mass 0.75 (Kleiber, 1975) and mass is in kg.…”
Section: Modeling Breath-hold Limitsmentioning
confidence: 99%
“…Across air-breathing, diving vertebrates, including three odontocetes, which included beluga (Noren et al, 2012), shallow diving emperor penguins (Aptenodytes forsteri; Ponganis et al, 2010) and freely diving Weddell seals (Leptonychotes weddelli; Castellini et al, 1992;Ponganis et al, 1993), a cADL that assumed an oxygen consumption rate of 2× Kleiber basal metabolic rate (BMR; Kleiber, 1975) best approximated experimentally determined ADLs. Thus, we assumed a diving metabolism of 2×BMR, as used for other cetaceans (Noren et al, 2002(Noren et al, , 2014, to estimate age-specific maximum breath-hold limits and bottom times at various dive depths, where BMR (l O 2 min −1 ) is 0.0101×mass 0.75 (Kleiber, 1975) and mass is in kg.…”
Section: Modeling Breath-hold Limitsmentioning
confidence: 99%
“…For walruses, there is no evidence of resource partitioning between sexes when they overlap in distribution during the winter. Thus, inter-sexual competition could be problematic for female walruses if prey availability decreases in the Arctic because the typical response of pinnipeds to low prey availability is to increase dive duration (Feldkamp et al, 1989;Crocker et al, 2006;Melin et al, 2008), and breeding females will be most at risk as they have elevated energetic requirements because of the costs of lactation (Noren et al, 2012(Noren et al, , 2014b. In addition, maternal foraging behaviors could be constrained by the physiological limits of their progeny.…”
Section: Diving Capacity Of Walrusesmentioning
confidence: 99%
“…The number of walruses converging on coastal haul-outs is expected to increase as summer sea ice continues to decline (Jay et al, 2011), but the ability of localized food supplies in these coastal regions to support large numbers of walruses over the long term is unknown (Ovsyanikov et al, 2008). Thus, these changes in behavior could affect the ability of walruses to meet daily energetic requirements (Noren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Note that maximum total body O 2 store and maximum O 2 uptake for a male killer whale were set at 137.3 and 25.52 l, respectively. Noren et al (2012) concluded that apnoea of 13.3 min in an adult male killer whale did not cause a rise in blood lactate levels. The maximum apnoea durations observed in our study were 6.1 and 5.3 min for males and females, respectively; it was assumed that lactate accumulation was not an issue.…”
Section: Influences Of Sex and Activity Level On Respiration Behaviourmentioning
confidence: 98%